Death in the city of light ebook The serial killer of nazi-occupied paris. - King, David (2011)
The gripping, true story of a brutal serial killer who unleashed his own reign of terror in Nazi-Occupied Paris. As decapitated heads and dismembered body parts surfaced in the Seine, Commissaire Georges-Victor Massu, head of the Brigade Criminelle, was tasked with tracking down the elusive murderer in a twilight world of Gestapo, gangsters, resistance fighters, pimps, prostitutes, spies, and other shadowy figures of the Parisian underworld. But while trying to solve the many mysteries of the case, Massu would unravel a plot of unspeakable deviousness.   The main suspect, Dr. Marcel Petiot, was a handsome, charming physician with remarkable charisma. He was the “People’s Doctor,” known for his many acts of kindness and generosity, not least in providing free medical care for the poor. Petiot, however, would soon be charged with twenty-seven murders, though authorities suspected the total was considerably higher, perhaps even as many as 150. Petiot's trial quickly became a circus. Attempting to try all twenty-seven cases at once, the prosecution stumbled in its marathon cross-examinations, and Petiot, enjoying the spotlight, responded with astonishing ease. Soon, despite a team of prosecuting attorneys, dozens of witnesses, and over one ton of evidence, Petiot’s brilliance and wit threatened to win the day. Drawing extensively on many new sources, including the massive, classified French police file on Dr. Petiot, Death in the City of Light is a brilliant evocation of Nazi-Occupied Paris and a harrowing exploration of murder, betrayal, and evil of staggering proportions.